Latent Semantic Analysis of OECD and G20 Member Countries Corporate Governance Codes - Vaniš, Jan; Kubíček, Aleš; Malý, Milan, 1936-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This thesis deals with quantifying convergence of corporate governance codes with the focus on OECD and G20 member countries. The thesis consists of theoretical and practical part. Theoretical part develops key terminology of corporate governance, corporate governance codes and later it also reviews scientific papers published on similar topics. There are two main goals for this thesis. Firstly, to quantify convergence of country codes towards the OECD Principles of Corporate Governance and secondly, to quantify convergence of nation codes between each other. This is done through identifying dominant themes in the whole corpus, analysis of weights of those themes in each country code and their evolution in time. The methodology used in thesis is Latent Semantic Analysis which is a statistical and mathematical technique for analyzing relationships between a set of documents and the terms they contain by producing a set of concepts related to the documents and terms. The programming language used in this thesis is R.
Vedoucí práce: Aleš Kubíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses